Reshaping Intercellular Interactions: Empowering the Exploration of Disease Mechanisms and Therapies Using Organoid Co-Culture Models - TAN Dengxu; MA Yifan; LIU Ke; ZHANG Yanying; SHI Changhong (Shiyan dongwu yu bijiao yixue)
The organoid co-culture model, as a novel tool for recreating a three-dimensional microenvironment to study cell-cell interactions, has demonstrated significant application potential in biomedical research in recent years. By simulating the in vivo tissue microenvironment, this model provides a more precise experimental platform for investigating complex cellular interactions, particularly in areas such as tumor immune evasion mechanisms, drug sensitivity testing, and the pathological characterization of neurodegenerative diseases, where it has demonstrated significant value. However, the organoid co-culture model still faces several challenges in terms of standardized procedures, large-scale cultivation, ethical guidelines, and future development. In particular, in the field of laboratory animal science, how to effectively combine organoids with traditional animal models, and how to select the most appropriate model for different research needs while exploring its potential for replacement, remain pressing issues. In the context of ethical approval and the replacement of animal experiments, the organoid co-culture model offers an experimental approach that better aligns with the "3R" principle (Replacement, Reduction, Refinement), potentially becoming an important tool for replacing traditional animal models. To this end, this paper reviews the latest advances and key challenges in this field, providing a detailed description of the construction methods for organoid co-culture models and discussing their applications in disease mechanism research and drug screening. The paper also systematically compares the organoid co-culture models with traditional animal models, exploring the criteria for selecting the appropriate model for specific applications. Furthermore, this paper discusses the potential value of organoid co-culture models as alternatives to animal experiments and anticipates future development trends of this technology. Through these discussions, the paper aims to promote the innovation and development of organoid co-culture technology and provide new perspectives and scientific evidence for future research.